Acceptance and Commitment Therapy Untuk Meningkatkan Acceptance of Illness Pasien Positif HIV - Dewantoro, Dhanang; Kurniawan, Afif (Persona:Jurnal Psikologi Indonesia, 2019)
AbstractThe problem that arise in female patients who diagnosed with positive HIV is their adjustment in physical dan psychological health condition, also stigma from the environment. Acceptance of illness has a significant influence on change in the psychological condition of patient, including being used to the limitations and dependence on other people due to their illness. This study aims to see the effectiveness of Acceptance and Commitment Therapy (ACT) to increase acceptance of illness. This study used the one group pretest-posttest design involved three respondents who had signed an informed consent. Instrument of this study used Acceptance of Disease and Impairments Questionnaire (ADIQ) developed by Boer et al. (2014). Data obtained were analyzed using the non-parametric Wilcoxon statistical test. The results showed that the intervention using Acceptance and Commitment Therapy (ACT) therapy was not significant for increasing acceptance of illness in female patients diagnosed with HIV (p = 0.109). Even so there was an increase in acceptance of illness scores of female patients with Positive HIV.Keywords: Acceptance and Commitment Therapy (ACT), acceptance of illness, and female diagnosed with positive HIVAbstrakPermasalahan yang muncul pada pasien perempuan dengan diagnosis positif HIV adalah penyesuaian terhadap kondisi kesehatan fisik dan psikologis pribadi serta stigma dari lingkungan. Penerimaan terhadap penyakit (acceptance of illness) mempunyai pengaruh besar terhadap kondisi psikologis pasien, termasuk menjadi terbiasa dengan keterbatasan dan ketergantungan pada orang lain karena penyakit yang dimiliki. Penelitian ini bertujuan untuk melihat efektivitas Acceptance and Commitment Therapy (ACT) untuk meningkatkan acceptance of illness. Penelitian ini menggunakan desain the one group pretest-posttest design untuk tiga subjek yang telah menandatangani informed consent. Pengumpulan data penelitian menggunakan alat ukur Acceptance of Disease and Impairments Questionnaire (ADIQ) yang dikembangkan Boer dkk. (2014). Data penelitian dianalisis menggunakan uji statistik non-parametric Wilcoxon. Hasil analisis data statistik menunjukan bahwa intervensi menggunakan terapi Acceptance and Commitment Therapy (ACT) tidak signifikan untuk meningkatkan acceptance of illness pada pasien perempuan yang didiagnosis positif HIV (p=0.109). Meski demikian terjadi peningkatan skor acceptance of illness pasien perempuan dengan HIV Positif.Kata Kunci:Acceptance and Commitment Therapy (ACT), acceptance of illness dan Perempuan dengan diagnosis positif HIV